The Implementation of the International Baccalaureate Curriculum of the Industry Era 4.0 - Risfita Wulandari; Muhammad Wildan Shohib; Azam Othman (Yayasan Letiges Konsultan Sosial, 2024)
This study aims to investigate the implementation of the International Baccalaureate Curriculum for Industry 4.0 Middle Years Program at Al-Firdaus Islamic High School Surakarta by examining how well the objectives and philosophy of the International Baccalaureate Curriculum are in line with the vision and mission of the school. This research uses a qualitative method with a phenomenological approach. Data were obtained from observations and interviews with the principal of the high school, the coordinator of the middle school program, and subject teachers. Data sources used primary and secondary data. The sampling techniques used were snowball sampling and data analysis, with data reduction, data presentation, and conclusion. The implementation of the International Baccalaureate Curriculum is well implemented and successful under the direction of the International Baccalaureate Organization, which continues to provide solutions and assistance to the demands of the Industrial Age 4.0 for the success of fostering international insights and helping students reflect on themselves based on their interests, identity, culture, respect for the environment, values, and multicultural experiences at school.